2008
DOI: 10.1016/j.cplett.2007.11.030
|View full text |Cite
|
Sign up to set email alerts
|

The boron buckyball has an unexpected Th symmetry

Abstract: The boron buckyball avoids the high symmetry icosahedral cage structure.The previously reported I h symmetric structure is not an energy minimum in the potential energy surface and exhibits a spontaneous symmetry breaking to yield a puckered cage with a rare T h symmetry. The HOMO-LUMO gap is twice as large as the reported value and amounts to 1.94 eV at B3LYP/6-31G(d) level. The valence orbital structure of boron buckyball is identical to the one in the carbon analogue.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
50
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 9 publications
3
50
0
Order By: Relevance
“…Its stability was further confirmed by comparing its cohesive energy with that of boron double rings, whose existence has been verified experimentally. Further calculations found that the I h B 80 cage has seven imaginary frequencies and exhibits a spontaneous symmetry breaking to achieve even lower energy [24,25]. In another work, Prasad and Jemmis studied a B 84 cluster that is a basic unit of bulk β-boron and found that it is deficient by 50 electrons according to the Wade-Mingos rule.…”
Section: Prediction Of New Stable Structuresmentioning
confidence: 98%
“…Its stability was further confirmed by comparing its cohesive energy with that of boron double rings, whose existence has been verified experimentally. Further calculations found that the I h B 80 cage has seven imaginary frequencies and exhibits a spontaneous symmetry breaking to achieve even lower energy [24,25]. In another work, Prasad and Jemmis studied a B 84 cluster that is a basic unit of bulk β-boron and found that it is deficient by 50 electrons according to the Wade-Mingos rule.…”
Section: Prediction Of New Stable Structuresmentioning
confidence: 98%
“…Cs 3 C 60 has a structure (26) that can be described using Figure 1, where the unit cell has C 60 units at the cube corners and at the bodycenter, and the Cs ions are at the corners of the icosahedron, so that both the C 60 units and the icosahedron have T h rather than I h symmetry. Cubic distortions from I h to T h symmetry have been predicted for the hypothetical molecules B 80 , Si 60 , and Ge 60 (27,28), and T h symmetry can be found experimentally in appropriately substituted fullerenes (29). In "octahedral" symmetry, T h occurs in hexa-coordinated complexes ML 6 , where L has a local C 2v symmetry, and the principal ligand planes include the heavy lines of Figure 2.…”
Section: Acknowledgmentmentioning
confidence: 99%
“…Later it has been defended that the geometry of the most stable structure seems to be a slight distortion of the I h configuration. Both Gopakamur et al [255,256] and Baruah et al [257] have further investigated the stability of the lowest energy isomers of B 80 , and claim that the icosahedral structure is unstable; the ground state configuration is reported to have, in fact, T h symmetry. However, the recent work of Sadrzadeh et al [258] has also investigated the issue, and report very small energy differences (lower than 30 meV) among the three lowest lying isomers (I h , T h , and C 1 ), with the icosahedral shape being, in fact, a close winner.…”
Section: Introductionmentioning
confidence: 99%